Application Of Correlation Data Mining the Covid-19 Pandemic With Student Achievement Level Using A Priori Method - Fiqri Agung Pangestu (CV. AFDIFAL MAJU BERKAH, 2022)
Education is carried out as early as possible so that a person gets the broadest insight into knowledge. The longer you have higher education will further improve the quality of human resources. Education can be obtained through lessons that are in accordance with the level of education and the learning material itself. The current condition of the COVID-19 outbreak has resulted in several agencies implementing Work From Home (WFH) or working from home, including educational institutions or agencies. The government provides a policy for every school to conduct online learning by using gadgets (laptops or cellphones) to access websites or learning links such as Whatsapp, Google Form, Google Classroom. A very significant difference in the student's learning process from usual, will affect the sharpening of students' ways of thinking about their learning. Students are required to be able to understand the material without direct interaction from the teacher, and the teacher is not able to provide the material as a whole to students. This will affect student achievement.